Pengaruh Konten Marketing Instagram Terhadap Citra Merek Rumah Sakit Indriati Solo Baru - Hanifah Puji Astuti; Anton Susanto; Hesty Latifa Noor (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Indonesia ranks fourth globally in terms of active Instagram users, with approximately 103 million users, positioning this platform as a strategic medium for hospitals to conduct promotion, health education, and audience engagement. Hospitals, particularly private institutions, have increasingly recognized the potential of social media in fostering strong brand images and maintaining public trust. This study aims to analyze the influence of marketing content on the brand image of Indriati Solo Baru Hospital, a private hospital that is active on Instagram and holds verified status. Employing a quantitative approach with an associative method, the research involved 100 respondents drawn from followers of the hospital’s official Instagram account, selected through incidental sampling. Data were collected via questionnaires and subsequently analyzed using simple linear regression. The results demonstrate that marketing content exerts a positive and significant impact on brand image, as reflected in the regression equation Y = 3.838 + 0.267X. Statistical analysis further revealed a significance value of 0.001 (<0.05) and a t-calculated score of 10.048, exceeding the t-table value of 1.984. The coefficient of determination (R²) was 0.507, indicating that marketing content accounts for 50.7% of the variance in brand image, while the remaining 49.3% is influenced by other factors beyond the scope of this study. Among the tested indicators, Decision Making and Life Factors demonstrated significant contributions, underscoring their role in shaping perceptions of brand image. Meanwhile, Persuasion, Reader Cognition, and Sharing Motivation functioned as supportive elements that reinforce but do not independently drive outcomes. These findings highlight the critical role of strategic content development in strengthening hospital brand image within digital spaces.